Evaluating the moderating role of information seeking platforms on university students' risk perception and anxiety during the COVID-19 pandemic in Ghana - Hagan, John Elvis; Quansah, Frank; Ankomah, Francis; Agormedah, Edmond Kwesi; Srem-Sai, Medina; Schack, Thomas (Frontiers in Communication, 2023)
The emergence of COVID-19 resulted in heightened usage of online information seeking platforms among students aimed at obtaining information about the virus. This situation further increased the levels of risk perception and anxiety levels as students managed to stay safe. This study examined the roles of information seeking platforms; specifically, social media platforms and professional platforms as regulators of the link between risk perception and anxiety among university students in Ghana. Participants were recruited from two universities in Ghana through a survey approach. The study conveniently sampled 778 participants who were administered questionnaires. The study results revealed that COVID-19 risk perception was found to be positively related to anxiety. The findings further showed that the use of specific online information platforms significantly moderated the link between risk perception and anxiety. Specifically, social media platforms significantly moderated the relationship between COVID-19 risk perception and anxiety level. Primarily, students who utilized social media as COVID-19 information source reported high anxiety levels in the presence of high risk perception as compared to those who did not use social media. Also, professional platforms usage acted as buffer in the positive link between COVID-19 risk perception and anxiety levels. In the presence of high risk perception, students who use professional platforms, as compared to those who did not use professional platforms, showed significantly low anxiety levels. Findings of this study suggest the key role social media and professional platforms played in shaping students’ perceptions about COVID-19. The findings call for the swift scrutiny of health-related information obtained from social media platforms. Both users and disseminators of health-related information on social media platforms have the responsibility of verifying the credibility of whichever information they post and/ or access. Risk perception should be integral part of effective risk communication planning in educational institution during disease outbreak.